The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1117/12.830967
|View full text |Cite
|
Sign up to set email alerts
|

Theory of light-induced deformations in azobenzene polymers: structure-property relationship

Abstract: We propose a microscopic theory of light-induced deformation of side-chain azobenzene polymers using a statistical model which takes the chemical architecture of azobenzene macromolecules explicitly into account. The theory provides the values of the light-induced stress larger than the yield stress. This result explains a possibility for the inscription of surface relief gratings in glassy side-chain azobenzene polymers. We show that the photo-elastic behavior of azobenzene polymers is very sensitive to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 30 publications
5
23
0
Order By: Relevance
“…The deformation is caused by the anisotropic character of photoisomerization: maximal probability for a transition from the trans- to cis-state is achieved at an orientation of the rodlike chromophore parallel to the electric vector of the light E . Under visible light irradiation, the rodlike chromophores are reoriented preferably perpendicular to the vector E after multiple trans–cis–trans photoisomerization cycles. Reorientation of chromophores results in the light-induced mechanical stress and deformation. Under ultraviolet (UV) irradiation, most of the trans-isomers are transformed to the cis-state and orientation anisotropy appears without the cyclic trans–cis–trans photoisomerisation process. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deformation is caused by the anisotropic character of photoisomerization: maximal probability for a transition from the trans- to cis-state is achieved at an orientation of the rodlike chromophore parallel to the electric vector of the light E . Under visible light irradiation, the rodlike chromophores are reoriented preferably perpendicular to the vector E after multiple trans–cis–trans photoisomerization cycles. Reorientation of chromophores results in the light-induced mechanical stress and deformation. Under ultraviolet (UV) irradiation, most of the trans-isomers are transformed to the cis-state and orientation anisotropy appears without the cyclic trans–cis–trans photoisomerisation process. …”
Section: Introductionmentioning
confidence: 99%
“…The strength of the orientation potential is proportional to the intensity of the light. Recently, this approach was used to study light-induced deformation of both un-cross-linked glassy azobenzene polymers and cross-linked azobenzene networks. Contribution of the light-induced orientation potential into the orientation free energy has been taken into account in ref , and the mechanical stress has been calculated. It was shown that the mechanical stress appearing at typical light intensities used in experiments ( I p ∼ 0.1 W/cm 2 ) is comparable with the yield stress (σ Y ∼ 50 MPa) typical for azobenzene polymers and can be even higher than the yield stress.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical approaches, presented in Section 2.1 , which use either angular-dependent kinetics of photoisomerization or the effective orientation potential, were successfully applied to describe the photo-deformation and ordering in azobenzene-containing polymers of various structures, including amorphous polymers [ 114 , 117 , 130 , 131 ], crosslinked isotropic polymer networks [ 132 , 133 ] and anisotropic azobenzene-containing liquid crystalline (LC) polymer networks [ 118 , 134 , 135 , 136 , 137 , 138 ]. The proposed theories can explain various experimental results for broad classes of azobenzene-containing polymers, as summarized briefly below.…”
Section: Resultsmentioning
confidence: 99%
“…As it was discussed in Section 2.1.3 , the orientation potential provides the mechanical stress of the magnitude 100 MPa—4 GPa at conventional light intensity , the stress being enough to deform irreversibly azobenzene polymers, which are deep in a glassy state [ 111 , 112 , 113 , 114 , 117 , 130 , 131 ]. Depending on the orientation distribution of azobenzene moieties inside polymer chains, preferably perpendicular or along the backbones of polymer chains, azo-polymers demonstrate either expansion or contraction along the polarization vector of the light [ 132 , 133 , 166 , 167 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation